Critiquing Practice Students Teachers: An Assessment of Preparedness - Crescini, Cleotilde L.; Ramos, Frederick O. (International Journal of Psychosocial Rehabilitation, 2020)
-- This study attempted to determine the level of readiness of the beginning teachers for future authentic jobs. Practice student teachers are routinely critiqued as part of the preparation for professional teaching. Fifty-six (56) critic teachers from various secondary schools in the province of Batangas and Laguna participated in the study. The Observation Form was used as main data gathering instrument. Weighted mean and ranking were used as statistical tools in analyzing data collected. By and large, the beginning teachers are now geared up to become members of the teaching profession. Winning personality, well composed poise, unwavering self-control, effectual speaking voice, inspiring enthusiasm, vitality to teach, and classroom management skills are highly manifested among beginning teachers. Noticeable among the beginning teachers are their intellectual curiosity, ability to make lessons more relevant and pragmatic, facility to elicit information from students, and can rationalize well fundamentally important themes. On the other hand, the students of beginning teachers exhibited remarkable interest and concentration on discussed subject matter and participated actively during the class discussion but with ample self-restraints. It is recommended then that permanent monitoring and evaluation of the teacher training program to raise furthest the bars performance especially in the licensure examination,